A molecular mediator modified lithium negative electrode and its preparation method and application
By modifying lithium ferrocene methanol on the surface of lithium metal negative electrode, the adsorbent ion transport interface is constructed, the electrolyte corrosion and dendritic growth problems of lithium negative electrode are solved, and long-term circulation and safety improvement of high surface capacity are achieved, which is suitable for industrialization Production.
Patent Information
- Application Number
- CN202411155049.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The high chemical reactivity of lithium metal negative electrodes leads to electrolyte corrosion and dendrites, causing safety hazards, and volume changes hinder performance under high surface capacity conditions, which are difficult to effectively solve in the existing technology.
By modifying lithium ferrocene methanol as the active site of the lithium matrix surface, an adsorbent ion transport interface is constructed, surface potential is adjusted, lithium ion deposition is inhibited, dendrites are reduced, and dendrites are formed and grown, achieving long-term effect of high surface capacity cycle.
It realizes the application of high current density and high magnification of lithium negative electrodes, stabilizes the interface, suppresses volume changes, improves safety and performance, and is suitable for industrial-scale production.
Smart Images

Figure CN118676455B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium negative electrodes, and more specifically, to a molecular mediator-modified lithium negative electrode and a preparation method and application thereof. Background Art
[0002] In recent years, the research and application of lithium-ion battery energy density has approached the theoretical limit of the material. The application of traditional negative electrode materials is restricted by their own properties, and people are in urgent need of negative electrode materials with higher energy density. Lithium metal negative electrode has a high theoretical specific capacity (3860mAh / g), which can improve the energy density of existing chemical batteries. However, the high chemical reaction activity of lithium metal negative electrode will aggravate the corrosion of electrolyte, and the growth of dendrites will cause short circuit and cause safety hazards. Under high surface capacity conditions, lithium negative electrode materials will produce drastic volume changes, which will hinder their performance. Summary of the invention
[0003] In view of the problems existing in the existing lithium metal negative electrode, the first purpose of the present invention is to provide a fast ion conversion type molecular mediator modified lithium negative electrode, which includes a matrix and a molecular mediator active site on the surface of the matrix. It has a higher interface ion diffusion rate, brings super strong lithium affinity, and can effectively adjust the surface potential, induce large-capacity, high-current uniform deposition of lithium ions, effectively stabilize the matrix interface, and inhibit volume changes.
[0004] The second object of the present invention is to provide a method for preparing a molecular mediator-modified lithium negative electrode. The preparation method provided by the present invention has simple process, low cost and is suitable for industrial-scale production.
[0005] The third object of the present invention is to provide an application of a molecular mediator-modified lithium negative electrode. The molecular mediator-modified lithium negative electrode of the present invention is applied to a lithium battery to achieve high current density and high rate application of the lithium negative electrode, effectively solving the problem of dendrite growth of the lithium negative electrode under such conditions.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] The invention discloses a molecular mediator modified lithium negative electrode, comprising a lithium matrix and a molecular mediator active site modified on the surface of the lithium matrix, wherein the molecular mediator active site comprises lithium ferrocene methoxide.
[0008] In the present invention, lithium ferrocene methoxide is used as a molecular mediator active site to modify the surface of the lithium matrix. The electrochemical interface formed by lithium ferrocene methoxide can achieve self-increase regulation of the surface potential under the stimulation of deposition stress, further inhibit the deposition of localized lithium ions, thereby reducing dendrite formation and growth, and achieving long-term circulation with high surface capacity.
[0009] In a preferred embodiment, the material of the lithium matrix is selected from at least one of pure lithium, lithium alloy, and lithium-boron composite material.
[0010] Further preferably, the chemical formula of the lithium alloy is LixMy, wherein M is selected from at least one of sodium, carbon, silicon, magnesium, aluminum, indium, silver, gold, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, tin, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, cadmium, antimony, hafnium, tantalum, tungsten, rhenium, iridium, platinum, mercury, thallium, lead, bismuth, and polonium; x is 0.65-0.95, and y is 0.05-0.35.
[0011] Further preferably, in the lithium-boron composite material, the total mass fraction of lithium and boron is ≥70%.
[0012] Further preferably, the lithium-boron composite material is composed of the following by mass percentage: Li 65%~95%, B 5%~35%, N 0~30%, wherein N is selected from at least one of sodium, carbon, silicon, magnesium, aluminum, indium, silver, gold, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, tin, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, cadmium, antimony, hafnium, tantalum, tungsten, rhenium, iridium, platinum, mercury, thallium, lead, bismuth, and polonium.
[0013] In a preferred embodiment, the thickness of the molecular mediator-modified lithium negative electrode is 10-200 μm.
[0014] Further preferably, the thickness of the molecular mediator modified lithium negative electrode is 10-60 μm. In this preferred embodiment, an ultra-thin molecular mediator modified lithium negative electrode is provided.
[0015] The present invention also provides a method for preparing a molecular mediator modified lithium negative electrode, wherein an oil solution containing ferrocene carboxaldehyde is coated on a lithium matrix and / or the surface of an object in direct contact with the lithium matrix, and then a heating reaction and / or a mechanochemical reaction are performed to obtain a molecular mediator modified lithium negative electrode, wherein the solvent of the oil solution containing ferrocene carboxaldehyde is selected from Class I base oil and / or ester oil.
[0016] In the present invention, an oil solution containing ferrocenecarboxaldehyde is obtained by dissolving ferrocenecarboxaldehyde in an oil solvent and then coated on the surface of a lithium substrate. The ferrocenecarboxaldehyde is then oxidized to ferrocenemethanol on the surface of lithium metal by heating or mechanical processing, and further reacts with lithium to form lithium ferrocenemethanol.
[0017] The inventors found that the use of oil solvents can not only bring about better reaction effects, but also help lubricate the lithium strip rolling process and facilitate further processing and production of thin lithium.
[0018] In a preferred embodiment, the solvent of the oil solution containing ferrocenecarboxaldehyde is mineral oil. The mineral oil used in the present invention is CAS8020-83-5.
[0019] In the present invention, the object in direct contact with the lithium matrix is, for example, a rolling roller.
[0020] Preferably, the thickness of the lithium matrix is 20 μm to 1.5 mm.
[0021] In a preferred embodiment, in the oil solution containing ferrocenecarboxaldehyde, the mass fraction of ferrocenecarboxaldehyde is 0.1-3%, preferably 0.5-1.5%.
[0022] In the present invention, the amount of ferrocene carboxaldehyde added needs to be controlled. If too much is added, the difficulty of the lithium ribbon thinning process will increase.
[0023] In a preferred embodiment, the oil solution containing ferrocenecarboxaldehyde further contains ferrocene, and the mass fraction of ferrocene in the oil solution containing ferrocenecarboxaldehyde is 0.1-3%, preferably 0.3-0.8%.
[0024] In the present invention, the added ferrocene itself does not react with lithium, but on the one hand it can produce intermolecular charge repulsion with ferrocene methanol in the oily liquid phase, which helps to separate ultra-thin lithium and roller, and more conveniently obtain ultra-thin molecular mediator modified lithium negative electrode. On the other hand, it can reduce the solubility of ferrocene methanol itself and better control the addition of trace ferrocene formaldehyde.
[0025] In a preferred embodiment, the heating reaction temperature is 15-120° C., preferably 50-90° C., and the heating reaction time is ≥1 h, preferably 3-6 h.
[0026] In a preferred embodiment, the mechanochemical reaction is selected from at least one of rolling, stamping and extrusion. The lithium matrix is deformed into a sheet or strip by the mechanochemical reaction, and during this process, ferrocene formaldehyde reacts with zero-valent lithium in the lithium matrix to form lithium ferrocene methoxide to modify the surface of the lithium matrix.
[0027] Preferably, the total deformation of the mechanochemical reaction is 5-100%.
[0028] Further preferably, when the oil solution containing ferrocenecarboxaldehyde does not contain benzaldehyde, the total deformation amount of the mechanochemical reaction is 5-35%, further preferably 10-20%. When the oil solution containing ferrocenecarboxaldehyde contains benzaldehyde, the total deformation amount of the mechanochemical reaction is 15-45%, and the total deformation amount of the mechanochemical reaction is 10-30% greater than the total deformation amount when no benzaldehyde is contained.
[0029] Within the total deformation range of the above preferred range, the electrochemical performance of the molecular mediator-modified lithium negative electrode is optimal. If benzaldehyde is added, the electrochemical performance can be optimized under a larger deformation amount.
[0030] The present invention also provides an application of a molecular mediator-modified lithium negative electrode, wherein the molecular mediator-modified lithium negative electrode is used as a negative electrode in an electrochemical energy storage device.
[0031] The electrochemical energy storage device includes but is not limited to lithium-ion batteries, lithium-sulfur batteries, lithium-air batteries, capacitors, etc.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention modifies the active sites of molecular mediators on the surface of the electrode substrate to construct an adsorptive ion transport interface, and adjusts the surface potential to effectively induce uniform deposition of lithium ions, thereby maintaining dynamic stability on the negative electrode surface and rapidly activating the lithium metal interface.
[0034] (2) The molecular mediator modified lithium negative electrode obtained by the method of the present invention is applied to lithium batteries, which can realize the high current density and high rate application of the lithium negative electrode, and effectively solve the problem of dendrite growth of the lithium negative electrode under such conditions.
[0035] (3) The preparation method provided by the present invention has a simple process and is convenient for preparation, and can be used in industrial production. In addition, the composite electrode material can be directly thinned during the in-situ reaction by applying a load, thereby preparing an ultra-thin electrode material, so that the thickness of the obtained composite electrode material can reach 20-100 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The surface morphology SEM image and element distribution EDS image of the molecular mediator modified composite lithium negative electrode with a thickness of 150 μm prepared in Example 1 of the present invention; wherein Figure 1 (a) Microscopic morphology under scanning electron microscope; Figure 1 (b) is the distribution of C elements; Figure 1 (c) is the distribution of O element; Figure 1 (d) is the distribution of Fe element.
[0037] Figure 2 The time-of-flight secondary mass spectrometry test of the molecular mediator modified composite lithium negative electrode with a thickness of 30 μm prepared in Example 1 determined that the thickness of the interface of the simultaneous reaction measurement of the generation of lithium ferrocene methoxide was 150 nm.
[0038] Figure 3 XPS of the molecular mediator modified composite lithium negative electrode with a thickness of 30 μm prepared in Example 1; Figure 3 (a) is C 1s; Figure 3 (b) Fe 2p; Figure 3 (c) Li 1s; Figure 3 (d) is O 1s.
[0039] Figure 4 The XPS of the electrode sheet in Comparative Example 1 of the present invention; wherein Figure 4 (a) is C 1s; Figure 4 (b) Fe 2p; Figure 4 (c) Li 1s; Figure 4 (d) is O 1s.
[0040] Figure 5 The electrode materials of Example 1 and Comparative Example 2 of the present invention are respectively at 5 mA / cm 2 、5mAh / cm 2 The symmetric cycle test performance diagram obtained under the test conditions; it can be seen from the figure that Example 1 can stably cycle for more than 2400 cycles, while Comparative Example 2 short-circuits around 40 cycles.
[0041] Figure 6 The electrode materials of Example 1 and Comparative Example 2 of the present invention are 2 、5 mAh / cm 2 The first lithium removal morphology under test conditions. Figure 6 (a) is the first delithiation morphology of Example 1, Figure 6 (b) is the first delithiation morphology of comparative example 2. It can be seen from the figure that Example 1 can achieve stable and comprehensive delithiation, while comparative example 2 shows extremely uneven void-like delithiation.
[0042] Figure 7 The electrode materials of Example 1 and Comparative Example 2 of the present invention are 2 、5 mAh / cm 2 The first lithium deposition morphology under the test conditions. Figure 7 (a) is the first lithium deposition morphology of Example 1, Figure 7 (b) is the first lithium deposition morphology of Comparative Example 2. It can be seen from the figure that Example 1 can achieve stable and uniform lithium deposition, while Comparative Example 2 has uncontrolled dendrite growth.
[0043] Figure 8 The electrode surface potential changes of the embodiment 1 and the comparative example 2 of the present invention using the Kelvin probe of the atomic force microscope and the force probe are shown. Figure 8 (a) is the change of electrode surface potential in Example 1, Figure 8 (b) is the change of electrode surface potential of comparative example 2. It can be seen from the figure that the initial surface potential of Example 1 is lower than that of Comparative Example 2, which helps to provide rapid deposition. At the same time, when stress (>140MPa) is applied to simulate the dendrite growth environment, the surface potential of Comparative Example 2 does not change significantly, while that of Example 1 increases by nearly 30 mV. The increased surface potential can hinder the further deposition of lithium ions in this area, thereby inhibiting dendrite growth.
[0044] Fig. 9 The cycle efficiency diagram of the full battery assembled with lithium iron phosphate of the electrode materials of Example 1 and Comparative Example 2 of the present invention at 2C rate, with the positive electrode active material loading of 10 mg / cm 2 After 550 cycles, the capacity retention rate of Example 1 is still greater than 80%, while the capacity retention rate of Comparative Example 2 decays to 11% after 245 cycles.
[0045] Fig.10 The electrode materials of Example 2 and Comparative Example 3 of the present invention are respectively at 3 mA / cm 2 、3 mAh / cm 2 Symmetrical cycle performance diagram tested under test conditions; Example 2 can stably cycle for more than 640 hours, while Comparative Example 3 shows significant polarization around 300 hours. DETAILED DESCRIPTION
[0046] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0048] Example 1
[0049] A lithium metal strip (Zhongneng Lithium, thickness 200 μm) was used, and the modified liquid phase was a mineral oil solution (CAS8020-83-5) of 1wt% ferrocene formaldehyde and 0.5wt% ferrocene. The mineral oil solution was applied to the surface of the lithium metal strip, and rolled at room temperature to obtain 150 μm and 30 μm composite sheets based on lithium metal (thickness controllable), and further punched to obtain a molecular mediator-modified composite lithium negative electrode with a diameter of 16 mm and a thickness of 150 μm and a molecular mediator-modified composite lithium negative electrode with a diameter of 16 mm and a thickness of 30 μm. After testing, the morphology SEM analysis and composition EDS analysis of the molecular mediator-modified composite lithium negative electrode with a thickness of 150 μm obtained in Example 1 are as follows: Figure 1 The time-of-flight secondary mass spectrometry analysis of the prepared molecular mediator-modified composite lithium anode with a thickness of 30 μm is shown in Figure 2As shown in Figure 2, COLi- and C5H5- represent the generated lithium ferrocene methoxide modified interface layer with a thickness of 150 nm. Its XPS analysis is shown in Figure 2. Figure 3 As shown, the occurrence of interfacial reaction can be further clearly determined from the Fe 2p map.
[0050] In a glove box, the molecular mediator-modified composite lithium negative electrode with a thickness of 150 μm prepared in Example 1 was assembled into a button-type symmetrical battery, Celgard 2400 was used as a separator, the electrolyte was 1M LiTFSI DME:DOL=1:1 (volume ratio), containing 2% LiNO3 additive, and the electrode was subjected to a symmetrical battery cycle test. -2 , 5 mAh cm -2 Under the test conditions, the test results are as follows Figure 5 As shown in the figure, the composite electrode of the embodiment can achieve stable cycling for more than 2400 cycles, and the polarization voltage still does not exceed 0.4 V. -2 , 5 mAh cm -2 Under the test conditions, the first lithium removal test is carried out as follows Figure 6 (a) shows a smoother delithiation interface. -2 , 5 mAh cm -2 Under the test conditions, the first lithium deposition test is carried out as follows Figure 7 (a) shows a smoother lithium deposition interface.
[0051] The surface potential of the electrode was measured by combining the Kelvin probe of the atomic force microscope and the force probe. Figure 8 As shown in (a), when stress (>140MPa) is applied to simulate the dendrite growth environment, Example 1 increases by nearly 30 mV. The increased surface potential can hinder the further deposition of lithium ions in this area, thereby inhibiting the growth of dendrites.
[0052] The full battery was assembled with the molecular mediator modified composite lithium negative electrode with a diameter of 16 mm and a thickness of 30 μm prepared in Example 1 and the LiFePO4 positive electrode, Celgard2400 was used as the separator, and the electrolyte was 1.0M LiPF6 EC:EMC:FEC=3:7:1 (volume ratio). Under the 2C test condition, the positive electrode active material loading was 10 mgcm -2 Perform full battery cycle testing, such as Fig. 9 The composite electrode full battery system of Example 1 can maintain stable cycling for 550 cycles or more, and the capacity retention rate can reach 80%.
[0053] Example 2
[0054] The modified liquid phase of lithium-boron alloy (80LiB thickness of 150 μm) is 1wt% ferrocene formaldehyde and 0.5wt% ferrocene in mineral oil solution (CAS8020-83-5). 150 μm 80LiB was rolled at room temperature to obtain a 100 μm composite sheet based on lithium metal (thickness controllable), and further punched to obtain a molecular mediator-modified composite lithium anode with a diameter of 16 mm and a thickness of 100 μm. At 3 mA cm -2 、3 mAh cm -2 Symmetrical battery cycle test was carried out under test conditions, and the test results are as follows Fig.10 As shown, Example 2 can be stably cycled for more than 640 hours, while Comparative Example 3 shows significant polarization around 300 hours.
[0055] Comparative Example 1
[0056] The lithium metal strip (Zhongneng Lithium Industry) (thickness 200 μm) was rolled at room temperature in a modified liquid phase (1 wt% ferrocene addition) to obtain a 50 μm composite sheet based on lithium metal (thickness controllable), and further punched to obtain an electrode sheet with a diameter of 16 mm. After testing, its XPS analysis is as follows Figure 4 As shown, there is no obvious peak in the Fe 2p spectrum, indicating that the addition of ferrocene alone does not generate a modified molecular mediator at the interface.
[0057] Comparative Example 2
[0058] The button-type symmetrical battery was assembled with 150 μm lithium metal pole pieces from commercial lithium ribbon (Zhongneng Lithium Industry) as positive and negative electrodes, Celgard2400 as the separator, and the electrolyte was 1M LiTFSI DME:DOL=1:1 (volume ratio), containing 2% LiNO3 additive. -2 , 5 mAh cm -2 Symmetrical battery cycle test was carried out under test conditions, and the test results are as follows Figure 5 As shown in Figure 1, comparative example 1 can only stably cycle for 40 cycles, after which the polarization voltage of the symmetrical battery begins to increase and the battery short-circuits. -2 , 5 mAh cm -2 Under the test conditions, the first lithium removal test is carried out as follows Figure 6 As shown in (b), a hollow and uneven lithium removal interface appears. Figure 7 (b) shows lithium deposition with severe dendrite growth.
[0059] The surface potential of the electrode was measured by combining the Kelvin probe of the atomic force microscope and the force probe. Figure 8(b) When stress (>140MPa) was applied to simulate the dendrite growth environment, the surface potential of Comparative Example 2 did not change significantly, and it did not have the function of regulating the interface potential.
[0060] The full battery was assembled with a commercial lithium ribbon (Zhongneng Lithium Industry) 120 μm lithium metal electrode as the negative electrode and LiFePO4 positive electrode, Celgard2400 was used as the separator, and the electrolyte was 1.0M LiPF6 EC:EMC:FEC=3:7:1 (volume ratio). The full battery cycle performance test was carried out. The test results are as follows Fig. 9 As shown in the figure. At 2C rate, the system capacity began to decrease after 245 cycles. After 150 cycles, the overall capacity of the system has decayed to 11%.
[0061] Comparative Example 3
[0062] A button-type symmetrical battery was assembled using lithium-boron alloy (80LiB thickness 100 μm) as the positive and negative electrodes, Celgard2400 as the separator, and the electrolyte was 1M LiTFSI DME:DOL=1:1 (volume ratio), containing 2% LiNO3 additive. -2 、3 mAh cm -2 Symmetrical battery cycle test was carried out under test conditions, and the test results are as follows Fig.10 As shown, comparative example 3 can only stably cycle for 300 cycles, after which the polarization voltage of the symmetrical battery begins to increase.
Claims
1. A molecular mediator modified lithium negative electrode, characterized in that: The invention comprises a lithium matrix and a molecular mediator active site modified on the surface of the lithium matrix, wherein the molecular mediator active site comprises lithium ferrocene methoxide.
2. The molecular mediator modified lithium negative electrode according to claim 1, characterized in that: The material of the lithium matrix is selected from at least one of pure lithium, lithium alloy, and lithium-boron composite material; The chemical formula of the lithium alloy is LixMy, wherein M is selected from at least one of sodium, carbon, silicon, magnesium, aluminum, indium, silver, gold, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, tin, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, cadmium, antimony, hafnium, tantalum, tungsten, rhenium, iridium, platinum, mercury, thallium, lead, bismuth, and polonium; x is 0.65-0.95, and y is 0.05-0.35; In the lithium-boron composite material, the total mass fraction of lithium and boron is ≥70%; The lithium-boron composite material is composed of 65% to 95% Li, 5% to 35% B, and 0% to 30% N by mass percentage, wherein N is selected from at least one of sodium, carbon, silicon, magnesium, aluminum, indium, silver, gold, scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, germanium, tin, yttrium, zirconium, niobium, molybdenum, technetium, ruthenium, rhodium, palladium, cadmium, antimony, hafnium, tantalum, tungsten, rhenium, iridium, platinum, mercury, thallium, lead, bismuth, and polonium.
3. The molecular mediator modified lithium negative electrode according to claim 1, characterized in that: The thickness of the molecular mediator-modified lithium negative electrode is 10-200 μm.
4. The method for preparing a molecular mediator-modified lithium negative electrode according to any one of claims 1 to 3, characterized in that: An oil solution containing ferrocenecarboxaldehyde is coated on a lithium matrix and / or a surface of an object in direct contact with the lithium matrix, and then a molecular mediator is obtained by a heating reaction and / or a mechanochemical reaction to obtain a lithium negative electrode modified with the molecular mediator. The solvent of the oil solution containing ferrocenecarboxaldehyde is selected from Class I base oil and / or ester oil.
5. The method for preparing a molecular mediator-modified lithium negative electrode according to claim 4, characterized in that: The thickness of the lithium matrix is 20 μm to 1.5 mm.
6. The method for preparing a molecular mediator-modified lithium negative electrode according to claim 4, characterized in that: In the oil solution containing ferrocenecarboxaldehyde, the mass fraction of ferrocenecarboxaldehyde is 0.1-3%; The oil solution containing ferrocene formaldehyde further contains ferrocene, and the mass fraction of ferrocene in the oil solution containing ferrocene formaldehyde is 0.1-3%.
7. The method for preparing a molecular mediator-modified lithium negative electrode according to claim 4, characterized in that: The temperature of the heating reaction is 15-120° C., and the heating reaction time is ≥1h.
8. The method for preparing a molecular mediator-modified lithium negative electrode according to claim 4, characterized in that: The mechanochemical reaction is selected from at least one of rolling, stamping and extrusion; The total deformation of the mechanochemical reaction is 5-100%.
9. The method for preparing a molecular mediator-modified lithium negative electrode according to claim 4, characterized in that: When the oil solution containing ferrocenecarboxaldehyde does not contain benzaldehyde, the total deformation of the mechanochemical reaction is 5-35%. When the oil solution containing ferrocenecarboxaldehyde contains benzaldehyde, the total deformation of the mechanochemical reaction is 15-45%. The total deformation of the mechanochemical reaction is 10-30% greater than the total deformation when no benzaldehyde is contained.
10. The use of a molecular mediator to modify a lithium negative electrode according to any one of claims 1 to 3, characterized in that: The molecular mediator-modified lithium negative electrode is used as the negative electrode in an electrochemical energy storage device.
Citation Information
Patent Citations
Silicon-based negative electrode material, preparation method and application thereof
CN116454240A
Electron mediator, electron mediator immobilized electrode, and biofuel cell using the electrode
US20050049313A1
